Phytochemical characterization and antidiabetic analysis of Bauhinia holophylla extract on the maternal-fetal outcomes of rats - Savazzi, Kamirri; DA CRUZ, Larissa L. [UNESP]; Moraes-Souza, Rafaianne Q.; Soares, Thaigra S.; Silva-Sousa, Jeferson José; Sinzato, Yuri Karen [UNESP]; Américo, Madileine Francely; Campos, Kleber Eduardo; Monteiro, Gean Charles [UNESP]; Lima, Giuseppina Pace P. [UNESP]; Damasceno, Débora Cristina [UNESP]; Volpato, Gustavo Tadeu (FapUNIFESP (SciELO), 2024)
This study aims to evaluate the phytochemical properties of Bauhinia holophylla (Bong.) Steud leaf extract, and their impact on maternal reproductive and fetal development in diabetic rats. For this, adult female Wistar rats (100 days of life) received streptozotocin (40 mg/Kg, intraperitoneal) for induction of diabetes, were mated and distributed into four groups: Nondiabetic; Nondiabetic given B. holophylla; Diabetic; and Diabetic given B. holophylla. The plant extract was given by gavage at increasing doses: 200, 400, and 800 mg/Kg. At day 21 of pregnancy, liver and blood samples were obtained for oxidative parameters and biochemical analysis, respectively. The uterus was removed for maternal-fetal outcomes. Phytochemical analysis showed a high content of phenolic components and biogenic amines. B. holophylla extract did not alter the glycemic levels but improved the lipid profile in diabetic animals. Besides that, the number of live fetuses and maternal weight gain were decreased in Diabetic group, and were not observed in animals treated. The group Diabetic treated presented a higher percentage of fetuses classified as adequate for gestational age compared to the Diabetic group. However, the treatment with plant extract caused embryo losses, fetal growth restriction, and teratogenicity in nondiabetic rats. Thus, the indiscriminate consumption requires carefulness.
Keywords: Hyperglycemia; malformations; medicinal plants; pregnancy; serotonin